Evidence for the Existence of Foetal Fibrinogen - Witt, I; Müller, H; Künzer, W (Thrombosis and Haemostasis, 1969)
Human fibrinogen was isolated from the blood of adults and from umbilical cord blood. The fibrinogen preparations obtained were clottable with thrombin to between 97 and 98% and homogeneous in acrylamide gel electrophoresis. Comparative analyses of these highly purified foetal and adult fibrinogen showed that they have the same quantitative amino acid composition and the same mobility in acrylamide gel electrophoresis at pH 9.2.Chromatography on DEAE-cellulose made it likely that foetal and adult fibrinogen have a slightly different electrical charge. The pH-dependency of the thrombin clotting time is strikingly different. The fingerprints of the tryptic peptides showed at least 3 peptides with different mobility in chromatography.From these data it is assumed that foetal and adult fibrinogen have a different molecular structure. Hitherto it cannot be decided if the two proteins have a different primary structure, which is most probable, or if they are chemical modifications.